2019
DOI: 10.1038/s41401-019-0213-0
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of specific cannabinoid receptor 2 agonist GW405833 on concanavalin A-induced acute liver injury in mice

Abstract: Cannabinoid receptor 2 (CB2R) is highly expressed in immune cells and plays an important role in regulating immune responses. In the current study, we investigated the effects of GW405833 (GW), a specific CB2R agonist, on acute liver injury induced by concanavalin A (Con A). In animal experiments, acute liver injury was induced in mice by injection of Con A (20 mg/kg, i.v.). The mice were treated with GW (20 mg/kg, i.p., 30 min after Con A injection) or GW plus the selective CB2R antagonist AM630 (2 mg/kg, i.p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…These markers were significantly increased in rats treated with atorvastatin, garlic oil and nanoformulation of garlic oil at a concentration of 0.65 mg/kg; while they were decreased in rats treated with nano-encapsulated garlic oil at concentrations of 0.18 and 0.46 ml/kg. Lymphocytic infiltration and necrosis, which indicates liver damage (Huang et al, 2019), were not observed in animals treated with 0.18 and 0.46 ml/kg of nanoemulsion. Hematoxylin and Eosin staining revealed a decrease in vesicular steatosis (presence of numerous vesicle of fat in the liver) at 0.65 ml/kg of the nanoformulation.…”
Section: Dyslipidemiamentioning
confidence: 85%
“…These markers were significantly increased in rats treated with atorvastatin, garlic oil and nanoformulation of garlic oil at a concentration of 0.65 mg/kg; while they were decreased in rats treated with nano-encapsulated garlic oil at concentrations of 0.18 and 0.46 ml/kg. Lymphocytic infiltration and necrosis, which indicates liver damage (Huang et al, 2019), were not observed in animals treated with 0.18 and 0.46 ml/kg of nanoemulsion. Hematoxylin and Eosin staining revealed a decrease in vesicular steatosis (presence of numerous vesicle of fat in the liver) at 0.65 ml/kg of the nanoformulation.…”
Section: Dyslipidemiamentioning
confidence: 85%
“…Using the Cre- loxP system to generate cell-type-specific deletion of CBRs in the hepatocyte, microglia, and dopamine neurons, we show that the application of Cre-loxP recombinant mouse strains unravels hitherto unknown physiological, behavioral and signaling mechanisms associated with CB2R function. For example, the upregulation of CB1R by HFHS diet in hepatocytes has an inverse relationship with the downregulation of CB2R by lipid overload in the co-expressed hepatocytes [ 51 , 52 ]. Therefore, we isolated adult rodent hepatocytes, neurons, and microglia to compare CB2R expression to those of CB1R.…”
Section: Discussionmentioning
confidence: 99%
“…At present, at least three unique synthetic CB2 agonists have reached clinic trials, including GW842166X, S-777469 and JBT-101 from ClinicalTrials.gov [22,70,103]. Anti-convulsant, neuroprotective [106]; antiinflammatory [96,97]; anti-nociceptive [96]; anti-dyskinesia [98]; osteoprotective [97]; alleviating septic lung injury [113] (e) GW-405833 Aminoalkylindole 4772/CB1 3.92/CB2 [24] 0.650 [24] Anti-nociceptive, anti-inflammatory [99]; protective effects on acute liver injury [114] (f) L-759,633…”
Section: Cb2-selective Agonistsmentioning
confidence: 99%
“…Rimonabant, AM-251 and AM-281 not only act as antagonists attenuating effects of CB1 agonists, but act as inverse agonists which can by themselves elicit responses in some CB1-containing tissues that are opposite in direction from those elicited by CB1 agonists [117]. More specifically, they appear to produce inverse cannabimimetic effects in at least some tissues by somehow reducing the constitutive Anti-convulsant, neuroprotective [106]; antiinflammatory [96,97]; anti-nociceptive [96]; anti-dyskinesia [98]; osteoprotective [97]; alleviating septic lung injury [113] (e) GW-405833 Aminoalkylindole 4772/CB1 3.92/CB2 [24] 0.650 [24] Anti-nociceptive, anti-inflammatory [99]; protective effects on acute liver injury [114] (f) L-759,633…”
Section: Cb1-selective Antagonists/inverse Agonistsmentioning
confidence: 99%
See 1 more Smart Citation